Development and psychometric properties of the transphobia scale among Indian adolescents - Yashwee Lonkar; Pushpalata Sharma; Jyoti Janswamy; Ruchi Sachan; Mahendra Kumar (Jurnal Keperawatan Padjadjaran, 2023)
Background: Most of the studies employed in the concerning area use foreign scales or translated versions for measurement of transphobia. It isreally unfortunate a democratic country like India does not possesses anystandardized scale to measure the transphobia of adolescents. Purpose: Therefore, this study includes the development and validation of ascale for the assessment of transphobia in Indian adolescents. Methods: A total 516 students of CBSE school aged 14-16 years were sampled. The items for the preliminary transphobia scale were drawn after interviewing the adolescents, consultation with a reference group and review from existing standardized scales. A total 516 participants were assessed for psychometric properties of the scale. Criterion validity was evaluated by using the ATTMW (attitude toward transgender men and women) Scale. Results: Exploratory Factor Analysis (EFA) revealed six factors accounting for 65.30% of observed variance. The final 31-item scale contained six factors: Interpersonal Ease, Gender Prejudices, Gender Obstinacy, Human Values, Gender Stereotype and Gender Abuse. Transphobia scale was highly reliable in terms of internal consistency (Cronbach’s alpha 0.927). Criterion validity with the ATTMW was statistically significant. Conclusion: As the conclusion of the study, the Indian transphobia scale can be used as a reliable and valid tool for the measurement of transphobia for Indian adolescents.